PERBEDAAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DENGAN TEKNIK GROUP CLOZE DAN TEKNIK GROUP SEQUENCING SISWA KELAS VIII SMP NEGERI 31 PADANG - Irfani Basri, Umul Khaira, Syahrul R., (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is as follows to, (1) the text describes the skills of reading comprehension group cloze exposition with the technique group class VIII SMP Negeri 31 Padang, (2) describing the text reading comprehension skills exposition with group sequencing techniques group class VIII SMP Negeri 31 Padang, (3) describes difference exposition text reading comprehension skills using techniques cloze group and group sequencing techniques eighth grade students of SMP Negeri 31 Padang. The results of this research consists of that, (1) the text reading comprehension skills with engineering group exposition cloze eighth grade students of group class VIII SMP Negeri 31 Padang is good and grades Baik with average (79.59), (2) the text reading comprehension skills with engineering group exposition sequencing eighth grade students of group class VIII SMP Negeri 31 Padang are in qualification More than Enough with the average (75.10), and (3) based on t-test, alternative hypothesis (HÂ1) is gained at the significant phase 95% and degrees of freedom (df) = (n1+n2)-2 because tcountÂ  > ttable (6,053 > 1,67).Â Kata kunci: perbedaan, membaca pemahaman teks eksposisi, teknik group cloze, teknik group sequencing